Assessment of the medicinal plant potential of the Delhi Ridge, Aravalli Range: traditional knowledge, biodiversity, and therapeutic applications - Anju Kumari Ojha; Chandra Bala (Lilloa)
Plant resources have been crucial for human societies, providing sustenance and natural remedies. With globalization, research on medicinal plants has increased, as over half of clinically approved drugs have plant origins. This study explores the ethnobotanical knowledge and medic- inal plant diversity in a specific region, emphasizing the demographic profiles of informants and the utilization of plant species for traditional medicine. A total of 92 participants, aged 30–85, were interviewed, revealing a predominance of male traditional healers and a significant correlation between age and medicinal plant knowledge. The research documented 70 medicinal plants belonging to 31 families, with Fabaceae being the most dominant with 16 species. Herbs (54%) were the prevalent growth form, followed by trees (26%). Leaves (32%) were the most commonly used plant parts, and decoction (34%) was the most popular preparation method. The results indicated a high use value (UV) for species such as Azadirachta indica (2.40) and a relative frequency of citation (RFC) value approaching unity for several key species, including Acacia nilotica and Prosopis cineraria. An informant consensus factor (ICF) analysis revealed that digestive diseases had the highest ICF value (0.94). The highest therapeutic redundancy (10.28 units) was observed in species like Euphorbia hirta, highlighting their versatile medicinal applications. This study underscores the importance of preserving traditional knowledge and plant diversity for future generations Ethnobotanical studies on indigenous plants are valuable for pharmaceutical development and sustainable healthcare.